2020
DOI: 10.1111/1758-5899.12748
|View full text |Cite
|
Sign up to set email alerts
|

How Corporate Governance Mechanisms of Banks Have Changed After the 2007–08 Financial Crisis

Abstract: Weak and ineffective corporate governance mechanisms in banks have been pointed out as the main factor that contributed to the 2007-08 financial crisis. The purpose of this study is to analyze empirically how the global financial crisis of 2007-08 has impacted on banks' governance mechanisms, comparing the differences between the two most important models of corporate governance (the shareholder and stakeholder models), and if these changes are related to improvements in banks' governance effectiveness. To car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Specifically, we examine the link between bank ESG scores on the one hand and bank risk‐taking and value on the other hand in a sample of European banks over 2007–2018. Our focus is the post financial crisis period given the reforms introduced to improve banks' corporate governance that have been implemented at the international, supranational and national levels since then (e.g., Fernández Sánchez, Odriozola Zamanillo, & Luna, 2020; Mülbert, 2009). As in this period regulators and the investing public broadened the role of corporate boards to include risk oversight (OECD, 2014), we also examine how executive board characteristics (size, independence and gender composition) interact with ESG scores to impact on bank risk‐taking and value.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we examine the link between bank ESG scores on the one hand and bank risk‐taking and value on the other hand in a sample of European banks over 2007–2018. Our focus is the post financial crisis period given the reforms introduced to improve banks' corporate governance that have been implemented at the international, supranational and national levels since then (e.g., Fernández Sánchez, Odriozola Zamanillo, & Luna, 2020; Mülbert, 2009). As in this period regulators and the investing public broadened the role of corporate boards to include risk oversight (OECD, 2014), we also examine how executive board characteristics (size, independence and gender composition) interact with ESG scores to impact on bank risk‐taking and value.…”
Section: Introductionmentioning
confidence: 99%
“…According to Marcinkowska (2012), corporate governance mechanisms essentially contributed to banking crisis in the world between 2007 and 2008. This led researchers and experts to carry out studies on what characterizes corporate governance mechanisms' effectiveness in the banking industry (Cotugno et al, 2020; de Haan & Vlahu, 2016; Fernandez Sanchez et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies in banks' governance have identified elements that contribute to the effectiveness of the governance mechanisms identified above. Hence, for board of directors, Fernandez Sanchez et al (2020) refer to smaller board size, expertise, independence, and blockholding as instruments that increase board of directors' effectiveness. To these characteristics of the board are to be added the board composition and the CEO duality.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, from a policy viewpoint, it contributes to the redesign of sector policies in the financial industry and the support of this industry by identifying specific initiatives to address the environment and institutional asymmetry. Solid governance practices are important to have effective bank systems that are critical to accomplish and sustain a higher level of public confidence in the banking system (Fernández Sánchez, Odriozola Zamanillo, & Luna, 2020).…”
Section: Introductionmentioning
confidence: 99%